Importance of Ahara in Today’s Life with Special Reference to Ayurveda.: Life Sciences -Ayurveda - Yewale, Dr Swapnali; Yewale, Dr Prasad (International Journal of Life Science and Pharma Research, 2023)
Ayurveda is an eternal science. Among all the vise concepts of Ayurveda, Trayaupsthambha has prime importance as itconsists of three pillars that are Ahara(Diet), Nidra(Sleep), and Brahmacharya (Celibacy). The longevity and happiness of lifedepend upon these three pillars. Each one has its importance; among them, Aharaachieved first position in Trayaupsthambha,which denotes its prime importance in Trayaupsthambha. Hence we must know the Ahara (diet) described in Ayurveda.Consuming a healthy diet in the right way can lead to good health; however, eating food that isn’t wholesome can make you sick.Ahara gives the body power, radiance, and Oja; it is essential for longevity and increases mental fortitude. Our ancient seerdescribes some rules regarding diet that every person should follow. If not, then the most beneficial object Ahara will turn into amost harmful object, which can cause various diseases. The healthy physical body and mind together are responsible for health.Our ancient seer, in their commentaries, proves that Ayurveda helps in keeping the equilibrium of all physiological functions ofSharir and Manas via proper Ahara. This article aims to study the importance of the ahara in today’s life. To achieve the goal of ahealthy life, the Ahara plays a vital role. This article aims to collect and analyze the literature review of the Sahara andunderstand the dietic rules explained in Ayurveda. This article discussed the significance of Ahara and diseases caused by pooreating habits. If Ahara is not consumed properly, numerous disorders, including the effects of Apathya-Ahara, may be noticed.